2011
DOI: 10.1503/cjs.028409
|View full text |Cite
|
Sign up to set email alerts
|

Surgeons’ and residents’ double-gloving practices at 2 teaching hospitals in Ontario

Abstract: Background: Surgeons and residents are at increased risk of exposure to blood-borne pathogens owing to percutaneous injury (PI) and contamination. One method known to reduce risk is double-gloving (DG) during surgery.Methods: All surgeons and residents affiliated with the University of Western Ontario (UWO) and McMaster University in 2005 were asked to participate in a Web-based survey. The survey asked respondents their specialty, the number of operations they participated in per week, their age and sex, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
2
16
0
3
Order By: Relevance
“…The proportion of all respondents who reported that they double glove routinely, 52%, is similar to that observed in previous studies, 1,2 whereas the proportion who reported ever double gloving, 78%, is higher. 1,2 In a large study (n = 509) conducted in Toronto and published over 20 years ago, Wright and colleagues 5 reported lower rates of routine double gloving (23.3%) and use of protective eyewear (66.4%) than those observed in the current study. The higher rates of double gloving in our study likely reflect increased concern for the personal safety of the surgical team and improved adherence to safety behaviours and best safety practices.…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…The proportion of all respondents who reported that they double glove routinely, 52%, is similar to that observed in previous studies, 1,2 whereas the proportion who reported ever double gloving, 78%, is higher. 1,2 In a large study (n = 509) conducted in Toronto and published over 20 years ago, Wright and colleagues 5 reported lower rates of routine double gloving (23.3%) and use of protective eyewear (66.4%) than those observed in the current study. The higher rates of double gloving in our study likely reflect increased concern for the personal safety of the surgical team and improved adherence to safety behaviours and best safety practices.…”
Section: Discussionmentioning
confidence: 38%
“…2 A 2011 study from Ontario also showed low rates of compliance with this safety practice. 1 Similar studies in other jurisdictions revealed low rates of double gloving. [3][4][5] The low level of double gloving is inconsistent with evidence supporting this practice.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…With more specimens, more detailed analysis of risk by glove type and other factors could be possible. Double gloving is an effective way to protect patients and practitioners and is common practice in our institution; however, double gloving, while common, is not universally practiced [7,13,18]. Mischke et al [13] found inner-glove puncture risk could be reduced by 71% with double gloving.…”
Section: Discussionmentioning
confidence: 99%
“…The use of power tools, handling sharp bone, and working in deep cavities all influence the risk of glove perforations in orthopaedic surgery [20]. Double gloving has been recommended in orthopaedic procedures to ameliorate the risk of perforation but compliance is not universal [7,18]. Duration of wear, degree of soilage, and other risk factors for glove perforation also have been reported [2,16].…”
Section: Introductionmentioning
confidence: 99%